Field-based pre-cooling for on-court tennis conditioning training in the heat - Duffield, R.; Bird, S. P.; Ballard, R. J. (Journal of Sports Science & Medicine, 2011)
The present study investigated the effects of pre-cooling for on- court, tennis-specific conditioning training in the heat. Eight highly-trained tennis players performed two on-court conditioning sessions in 35oC, 55% Relative Humidity. Sessions were randomised, involved either a pre-cooling or control session, and consisted of 30-min of court- based, tennis movement drills. Pre-cooling involved 20-min of an ice-vest and cold towels to the head/neck and legs, followed by warm-up in a cold compression garment. On-court movement distance was recorded by 1Hz Global Positioning Satellite (GPS) devices, while core temperature, heart rate and perceptual exertion and thermal stress were also recorded throughout the session. Additionally, mass and lower-body peak power during repeated counter-movement jumps were measured before and after each session. No significant performance differences were evident between conditions, although a moderate-large effect (d = 0.7-1.0; p > 0.05) was evident for total (2989 ± 256 v 2870 ± 159m) and high-intensity (805 ± 340 v 629 ± 265m) distance covered following pre-cooling. Further, no significant differences were evident between conditions for rise in core temperature (1.9 ± 0.4 v 2. 2 ± 0.4oC; d > 0.9; p > 0.05), although a significantly smaller change in mass (0.9 ± 0.3 v 1. 3 ± 0.3kg; p < 0.05) was present following pre-cooling. Perceived thermal stress and exertion were significantly lower (d > 1.0; p < 0.05) during the cooling session. Finally, lower-body peak power did not differ between conditions before or after training (d < 0.3; p > 0.05). Conclusions: Despite trends for lowered physiological load and increased distances covered following cooling, the observed responses were not significantly different or as explicit as previously reported laboratory-based pre-cooling research